A Qualitative Inquiry on Academic Social Identity A Case Study on Students of Department of Psychology Universitas Pembangunan Jaya - Gita Widya Laksmini Soerjoatmodjo (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2020)
What does being a student of Psychology in Universitas Pembangunan Jaya (UPJ) mean to you? This question was given to 33 students-cum-participants of this research. The background was that academic social identity – defined as how individuals identify to their academic institutions and/or subject areas they undertake during the time spent throughout their educational process – is key to their achievements. The objective was to understand the academic social identity of UPJ Department of Psychology students, particularly those who took Qualitative Research Method course in 2019/2020 Academic Year, to better understand their trajectories. This writing used qualitative research method with youth participatory action approach, applying photovoice as data collecting method, which produced visual and textual data analyzed from interpretative phenomenological perspective. The result showed that their academic social identity comprised of the following stages: understanding what Psychology is, their own personal and non-personal reasons to choose this discipline and then understanding their roles as students – both in Department Psychology and in UPJ. Discussion touched upon the stage that seemed to be particularly painstaking: understanding their roles as students – opening doors to provide student service supports to ensure smoother transition. It was concluded that academic social identity is a never-ending process.